Assessment of electrical stimulation in the treatment of the dysphagia caused by stroke - Soares, Thaís Miranda Curvelo; Conceição, Tatiana Maíta Alves; Cardoso, Fabrício; Beresford, Heron (Acta Fisiátrica, 2009)
The neurogenic dysphagia understands the alterations of the swallowing that happen because of a neurological disease. This dhysphagia type is particularly debilitating. It can cause death or increased health care costs current tracheal aspiration. This pathology is common and it consists of a complication potentially fatal for stroke, happening in approximately 50% of those patient ones. Among the possible treatments, the tactile-thermal stimulation and biofeedback they have a frequent success, varying from 0% to 83%. Studies register high success of this treatment with patients that suffered stroke, what doesn't usually include the most severe dysphagia. The use of the electrical stimulation in treating dyspha-gia was first reported in 1996 by Freed et al and, later, by Park et al. Both compared the use of the electric stimulation with the one of the tactile-thermal stimulation. The objective of that electric stimulation was to enhance the afferent arm of the swallow reflex in stroke patients with dysphagia associated with delayed initiation of swallowing. Being still this a treatment alternative little explored, the objective of that study was to accomplish a bibliographical revision about the use of the electric stimulation in the treatment of the dysphagia in patients that suffered stroke. Conclusion: The dysphagia caused by stroke is directly associated to the increase of the medical complications and needs the attention the Health’ professionals. The electrical stimulation a important instrument of work for dysphagia. It must to be explore its, because it has a good effective.